The mechanism of silicon on alleviating cadmium toxicity in plants: A review - Hou, Lei; Ji, Shengzhe; Zhang, Yao; Wu, Xiuzhe; Zhang, Li; Liu, Peng (Frontiers in Plant Science, 2023)
Cadmium is one of the most toxic heavy metal elements that seriously threaten food safety and agricultural production worldwide. Because of its high solubility, cadmium can easily enter plants, inhibiting plant growth and reducing crop yield. Therefore, finding a way to alleviate the inhibitory effects of cadmium on plant growth is critical. Silicon, the second most abundant element in the Earth’s crust, has been widely reported to promote plant growth and alleviate cadmium toxicity. This review summarizes the recent progress made to elucidate how silicon mitigates cadmium toxicity in plants. We describe the role of silicon in reducing cadmium uptake and transport, improving plant mineral nutrient supply, regulating antioxidant systems and optimizing plant architecture. We also summarize in detail the regulation of plant water balance by silicon, and the role of this phenomenon in enhancing plant resistance to cadmium toxicity. An in-depth analysis of literature has been conducted to identify the current problems related to cadmium toxicity and to propose future research directions.